IGFN1_v1 is required for myoblast fusion and differentiation. - Xiang Li; Jane Baker; Tobias Cracknell; Andrew R Haynes; Gonzalo Blanco (PLoS ONE, 2017)
Igfn1 is a complex locus that codes for multiple splicing variants of Immunoglobulin- and Fibronectin-like domain containing proteins predominantly expressed in skeletal muscle. To reveal possible roles for Igfn1, we applied non-selective knock-down by shRNAs as well as specific targeting of Igfn1 exon 13 by CRISPR/Cas9 mutagenesis in C2C12 cells. Decreased expression of Igfn1 variants via shRNAs against the common 3'-UTR region caused a total blunting of myoblast fusion, but did not prevent expression of differentiation markers. Targeting of N-terminal domains by elimination of exon 13 via CRISPR/Cas9 mediated homologous recombination, also resulted in fusion defects as well as large multinucleated cells. Expression of IGFN1_v1 partially rescued fusion and myotube morphology in the Igfn1 exon 13 knock-out cell line, indicating a role for this variant in myoblast fusion and differentiation. However, in vivo overexpression of IGFN1_v1 or the Igfn1 Exon 13 CRISPR/Cas9 targeting vector did not result in significant size changes in transfected fibres.